2008
DOI: 10.1002/crat.200800301
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies on the influence of temperature and growth rate history on crystal growth

Abstract: Crystallization experiments of sucrose were performed in a batch crystallizer to study the effect of temperature and growth rate history on the crystal growth kinetics. In one of the growth methods adopted, the isothermal volumetric growth rate (R V ) is determined as a function of supersaturation (S) at 35, 40 and 45 ºC. In the other, crystals are allowed to grow at constant supersaturation by automatically controlling the solution temperature as the solute concentration decreased. Using the latter method R V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…4 and the obtained results are presented in Table 1. The effect of growth rate history [6,[19][20][21][22] is clearly shown in both Figs. 2 and 3, when all runs are compared with the run of highest initial supersaturation.…”
Section: Kinetics and Thermodynamicsmentioning
confidence: 80%
“…4 and the obtained results are presented in Table 1. The effect of growth rate history [6,[19][20][21][22] is clearly shown in both Figs. 2 and 3, when all runs are compared with the run of highest initial supersaturation.…”
Section: Kinetics and Thermodynamicsmentioning
confidence: 80%
“…3, 4 and 5 Fig. demonstrated using kinetic data [35][36][37][38] and high-resolution microscopy, 39,40 the crystallization kinetics of sucrose is significantly affected by the growth rate history and by the alteration of surface roughness. Simulation II was performed using the CAMUS parameters chosen to fit the experimental data.…”
Section: Crystal Growth Curves Showing Maximum Growth Rates At Intermmentioning
confidence: 99%
“…Furthermore, the authors assumed that the surface roughness acts in the manner of a strong impurity, which they underlined by treating the mechanism as being equivalent to the surface adsorption of an impurity using the Kubota‐Mullin model . Martins et al as well as Flood speak of strains or interfacial tensions on the crystal surface, which likely cause an increase in the energetic barrier for growth and thus decrease the crystal growth rate. Another example for reduced growth rates due to an increase in surface roughness is given by Garside who found that milled seed crystals of potassium chloride grew more slowly on average than unmilled crystals.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the surface quality of the crystals, there exist two opinions that are discussed controversially in the literature. On the one hand, some authors claim that the growth rate decreases with an increase in surface roughness , , . On the other hand, there are authors who found that crystal‐growth rates increase with an increase in surface roughness , .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation